High-temperature intermittent drying: quality characterization of crumb rubber - Ng, Mei Xiang (2019)
In rubber research, drying is one of the most prominent stage to preserve the material. Numerous drying studies had been conducted by industrial specialists and researchers for decades, but the difficulties in producing consistent quality rubber remained unresolved. Hot air drying is the preferred artificial drying method to produce dried crumb rubber, but the final products tends to have wet rubber trapped in the dried rubber, which was undesirable. Prolonged drying at high hot air heating temperature was typically used to prevent the wet rubber pieces in dried rubber. However, the prolonged drying period leads to severe deterioration of rubber’s properties. One way to overcome this quality problem is to apply two-stage drying techniques. The basis of this research work was to study the possibility of quality enhancement through two-stage intermittent vacuum convective drying of crumb rubber via time-varying stepwise temperature profile. The main objectives were to compare the quality and drying kinetics of crumb rubber subjected to the two-stage vacuum convective drying (VCD) techniques. The experimental strategy was started with drying the crumb rubber using vacuum drying (VD), hot air drying (HAD) and two-stage VCD. The application of two-stage VCD in rubber drying gave the shortest drying time compared to VD and HAD. It was found that the two-stage VCD gave the lowest colour change and high plasticity retention index. Thus, further experimental works were carried out based on two-stage VCD. To objectively access the quality changes of rubber, the effect of varying operating parameters, including vacuum pre-drying duration, hot air drying temperature and rubber sample diameter were investigated for two-stage continuous and intermittent VCD at high drying temperature (90 - 150°C). Their drying kinetics (drying time, drying rate, effective moisture diffusivity) and product quality (visual attributes, textural attributes) were considered. The results indicated that the drying kinetics and the overall quality results of dried rubber under two-stage intermittent VCD at high temperature performed better than the corresponding continuous tests. Using two-stage intermittent VCD, dried rubber had an acceptable colour, hardness and stickiness that required further test plan. Using a time-varying stepwise temperature profile, the rubber samples were dried sequentially with vacuum pre-drying at 90°C (30 min), followed by hot air drying at 150°C (60 min), 130°C (40 min) and 110°C (80 min). For every 15 min in the hot air convective dryer, the heat input was switched off for 5 min tempering intervals, which is intermittent ratio of 0.75. The time-varying stepwise intermittent process resulted in an acceptable colour of rubber products with moderate hardness and high stickiness. The total colour change (ΔE) values of the dried crumb rubber was 7.82, which was lowered than hot air drying and vacuum drying (12.75 and 9.93). The dried crumb rubber hardness and stickiness values were 69.42 and -27.55 g, respectively whereas continuous hot air dried crumb rubber had hardness and stickiness values of 620.69 and -140.29 g, respectively. The results indicate that the time-varying stepwise temperature profile helps in maintaining the sample temperature to prevent severe oxidative degradation to the samples. The samples tend to form impermeable rubber layer when undergone prolonged drying. The main contribution of this study is to provide comprehensive information on the high temperature drying characteristics of rubber, concerning both drying kinetics and the product quality. The effect of controllable factors such as vacuum pre-drying duration, hot air heating temperature and sample diameter were investigated for both two-stage continuous and intermittent VCD. The industry should adopt two-stage VCD approach with time varying stepwise profile for better rubber quality and shorter drying time.